Answer: 30
Step-by-step explanation:
5x + 3(x – 5) = 6x + 2x – 15
Part A: Solve the equation and write the number of solutions. Show all the steps. (6 points)
Part B: Name one property you used to solve this equation. (4 points)
Hi there
5x+3(x-5)=6x+2x-15
Simplify both sides of the equation
5x+3(x-5)=6x+2x-15
Distribute
5x+3x-15=6x+2x-15
Combine like terms
(5x+3x)-15= (6x+2x)-15
8x-15=8x-15
Subtract 8x from both sides
8x-15-8x=8x-15-8x
-15=-15
Add 15 to both sides
-15+15=-15+15
0=0
All real numbers are solutions
To solve this equation I used " The distributive property"
I hope that's help !
Good night !
cos(θ) =
tan(θ) =
csc(θ) =
sec(θ) =
cot(θ) =
Answer:
Step-by-step explanation:
Alright, lets get started.
Please refer the diagram I have attached.
The point (8, -15) shows it is in 4th quadrant.
side X is 8 and side Y is -15.
We can find side R with help of Pythagorean theorem.
Taking square root,
sinΘ=
cosΘ=
tanΘ=
cscΘ=
secΘ=
cotΘ=
Answer
Hope it will help :)
rectangular sides and bottom of the tent have the dimensions
of 6 feet by 4 feet. The surface area of the tent is
square feet.
The surface area of the tent is 86 ft²
Therefore,
The base and top are triangular.
Therefore,
area of base = 1 / 2 bh = 1 / 2 × 4 × 3.5 = 7 ft²
area of the tope = 7 ft²
Therefore, the other three rectangular sides are calculated as follows:
area = 6 × 4 = 24 ft²
area = 6 × 4 = 24 ft²
area = 6 × 4 = 24 ft²
Therefore,
Surface area = 7 + 7 + 24 + 24 + 24 = 86 ft²
learn more on triangular prism:brainly.com/question/14795784